Mechanism of Action of Secreted Newt Anterior Gradient Protein. - Kathrin S Grassme; Acely Garza-Garcia; Jean-Paul Delgado; James W Godwin; Anoop Kumar; Phillip B Gates; Paul C Driscoll; Jeremy P Brockes (PLoS ONE)
Anterior gradient (AG) proteins have a thioredoxin fold and are targeted to the secretory pathway where they may act in the ER, as well as after secretion into the extracellular space. A newt member of the family (nAG) was previously identified as interacting with the GPI-anchored salamander-specific three-finger protein called Prod1. Expression of nAG has been implicated in the nerve dependence of limb regeneration in salamanders, and nAG acted as a growth factor for cultured newt limb blastemal (progenitor) cells, but the mechanism of action was not understood. Here we show that addition of a peptide antibody to Prod1 specifically inhibit the proliferation of blastema cells, suggesting that Prod1 acts as a cell surface receptor for secreted nAG, leading to S phase entry. Mutation of the single cysteine residue in the canonical active site of nAG to alanine or serine leads to protein degradation, but addition of residues at the C terminus stabilises the secreted protein. The mutation of the cysteine residue led to no detectable activity on S phase entry in cultured newt limb blastemal cells. In addition, our phylogenetic analyses have identified a new Caudata AG protein called AG4. A comparison of the AG proteins in a cell culture assay indicates that nAG secretion is significantly higher than AGR2 or AG4, suggesting that this property may vary in different members of the family.